Hubungan Kontrol Diri dengan Kesejahteraan Digital pada Gen Z - Annisa Dwika Rani; Komarudin Komarudin (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
The use of digital media among Gen Z continues to increase and has an impact on various aspects of life that can lead to addiction and decreased digital well-being. Gen Z's self-control in using gadgets remains low to moderate, leaving them vulnerable to the influence of digital content. Low self-control can affect Gen Z digital well-being. This study aims to determine the relationship between self-control and digital well-being among Gen Z. It uses a correlational quantitative research design with a purposive sample of 355 Gen Z participants. The research data collection was measured using the DWB scale with dimensions developed by Smits and the self-control scale with dimensions developed by Tangney, which the researcher compiled. The data analysis technique for testing the hypothesis used Pearson's Product-Moment with the SPSS 20 Windows application. The data analysis revealed a positive and significant relationship between self-control and DWB. The study found that the majority of Gen Z had moderate levels of self-control and DWB. The suggestion for further researchers is to increase the number of respondents across different age ranges.